Comparison of anterior and posterior approach in the treatment of acute and chronic cervical spinal cord injury: a meta-analysis - Ding, Yi; Li, Ning; Hu, Wenjing; Jiang, Wenkang; Zhu, Qianmiao; Jiang, Ting; Cheng, Huilin (Frontiers in Surgery, 2024)
ObjectiveA cervical spinal cord injury (CSCI) is a traumatic catastrophe that often leads to neurological dysfunction. The optimal surgical procedure for the treatment of CSCI remains debatable. The aim of this meta-analysis is to compare the neurological outcomes, complications, and clinical factors between anterior and posterior approach in CSCI treatment.MethodsWe searched PubMed, Embase, Web of Science and Cochrane library from their inceptions to october 2023. Preoperative and postoperative Spinal Injury Association (ASIA) and Japanese Orthopedic Association (JOA) scores, and calculated recovery rates (RRs) were compared between the two strategies, and differences in complication rates, operation time, intraoperative blood loss and length of stay were also analyzed.ResultsA total of five studies containing 613 patients were included, with 320 patients undergoing the anterior approach and 293 patients undergoing the posterior approach. Four of the studies included were retrospective cohort studies of high quality as assessed by the Newcastle Ottawa Scale. Additionally, there was one randomized controlled trial evaluated with the Cochrane Risk of Bias tool. Although both anterior and posterior approaches effectively facilitate spinal decompression and promote good neurological recovery, there was no significant difference in the incidences of neurological dysfunction and complications or other clinical features between the two approaches.ConclusionThere is no evidence thus far supports one approach over the other. Large-scale randomized controlled studies are warranted to further distinguish these two methods.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO [CRD42023438831].